ANALISIS KOMPETENSI DIGITAL PENDIDIK DALAM PEMANFAATAN TEKNOLOGI INFORMASI DI PEMBELAJARAN DARING DENGAN UJI CHI-SQUARE - Christian Arby Putra Liming; Boyke Danan Filtranda; Bayu Wira Aji Yudhoyono; Jadiaman Parhusip (Informatika: Jurnal Teknik Informatika dan Multimedia, 2024)
This study aims to analyze the relationship between geographical location and educators' level of digital competence in online learning in Indonesia. Using a quantitative approach and Chi-Square test, this study involved 400 respondents consisting of educators in urban and rural areas. The analysis showed a significant relationship, with educators in urban areas having higher levels of digital competence. Factors such as access to technology infrastructure and distribution of digital training were the main determinants of this difference. These findings underscore the importance of equitable distribution of digital infrastructure and technology training to support inclusive online education transformation.